Electronically Tunable Mixed-Mode Universal Filter Employing a Single Active Block and a Minimum Number of Passive Components - Mohammad Faseehuddin; Norbert Herencsar; Musa Ali Albrni; Jahariah Sampe (Applied Sciences, 2020)
A recently developed active building block, namely Voltage Differencing Extra X Current Conveyor (VD-EXCCII), is employed in the design of multi input single output (MISO), electronically tunable mixed-mode universal filter. The filter provides low pass (LP), high pass (HP), band pass (BP), band reject (BR) and all pass (AP) responses in current-mode (CM), voltage-mode (VM), trans-impedance-mode (TIM) and trans-admittance-mode (TAM). The filter employs a single VD-EXCCII, three resistors and two capacitors. Additionally, a CM single input multi output (SIMO) filter can be derived from the same circuit topology by only adding current output terminals. The attractive features of the filter include: (i) the ability to operate in all four modes, (ii) the tunability of the Q factor independent of pole frequency, (iii) the low output impedance for the VM filter, (iv) the high output impedance current output for CM and TAM filters and (v) no requirement for double/negative input signals (voltage/current) for response realization. The VD-EXCCII and its layout is designed and validated in Cadence Virtuoso using 0.18 µm pdk from Silterra Malaysia with a supply voltage of ±1.25 V. The operation of the filter is examined at the 8.0844 MHz characteristic frequency. A non-ideal parasitic and sensitivity analysis is also carried out to study the effect of process and components spread on the filter performance.